Costs and advance directives at the end of life: a case of the 'Coaching Older Adults and Carers to have their preferences Heard (COACH)' trial. Issue 1 (June 2015) - Kaambwa, Billingsley; Ratcliffe, Julie; Bradley, Sandra; Masters, Stacey; Davies, Owen; Whitehead, Craig; Milte, Catherine; Cameron, Ian; Young, Tracey; Gordon, Jason; Crotty, Maria
Abstract Background Total costs associated with care for older people nearing the end of life and the cost variations related with end of life care decisions are not well documented in the literature. Healthcare utilisation and associated health care costs for a group of older Australians who entered Transition Care following an acute hospital admission were calculated. Costs were differentiated according to a number of health care decisions and outcomes including advance directives (ADs). Methods Study participants were drawn from the Coaching Older Adults and Carers to have their preferences Heard (COACH) trial funded by the Australian National Health and Medical Research Council. Data collected included total health care costs, the type of (and when) ADs were completed and the place of death. Two-step endogenous treatment-regression models were employed to test the relationship between costs and a number of variables including completion of ADs. Results The trial recruited 230 older adults with mean age 84 years. At the end of the trial, 53 had died and 80 had completed ADs. Total healthcare costs were higher for younger participants and those who had died. No statistically significant association was found between costs and completion of ADs. Conclusion For our frail study population, the completion of ADs did not have an effect on health care utilisation and costs. Further research is needed to substantiate these findings in larger and more diverse clinical cohorts of older people. Trial registration This study was registered on 13/12/2007 with the Australian New Zealand Clinical Trial Registry (ACTRN12607000638437 ).